Inter-eye Differences in Ocular Biometric Parameters of Concomitant Exotropia - Gong, Weifen; Chen, Haoyu; Yang, Fan; Lin, Shibin; Li, Chao; Wang, Geng (Frontiers in Medicine, 2022)
Purpose: To evaluate the ocular biometric parameters in patients with constant and intermittent exotropia by the measurement of swept-source optical coherence tomography (SS-OCT) optical biometer OA-2000 and compare with the normal control subjects. Design: Cross-sectional case-control study. Participants: Fifty-five constant and 24 intermittent exotropia patients with central fixation and 77 orthotropic normal control participants aged 4-18 years old. Methods: Non-contact and high-resolution optical biometric OA-2000 measurements were conducted under uniform ambient light conditions. Statistical analysis included intraclass correlation coefficient (ICC), Bland-Altman plot and independent t-tests. Main Outcome Measures: Spherical equivalent (SE), ocular biological parameters such as pupil diameter (PD), anterior chamber depth (ACD), lens thickness (LT) and axial lengths (AL). The absolute values of inter-eye differences for SE, PD, ACD, LT and AL were recorded as AnisoSE, AnisoPD, AnisoACD, AnisoLT and AnisoAL. Results: AnisoSE (0.878 vs 0.577, P = 0.019), AnisoAL (0.395 vs 0.208, P = 0.001), AnisoACD (0.060 vs 0.032, P < 0.001), AnisoLT (0.060 vs 0.031, P = 0.002) and AnisoPD (0.557 vs 0.340, P = 0.002) were significantly larger in concomitant exotropia patients. SE, AL, ACD, LT and PD showed excellent binocular correlation with ICC values ranged from 0.943 to 0.987 in control participants and 0.767 to 0.955 in concomitant exotropia patients. Bland-Altman plots showed the wider range of agreement in concomitant exotropia patients than the control participants (SE: 5.0288 vs 3.3258; AL: 2.2146 vs 1.3172; ACD: 0.3243 vs 0.1682; PD: 2.4691 vs 1.9241; LT: 0.3723 vs 0.1858) Conclusion: Concomitant exotropia patients showed larger inter-eye differences in SE, ACD, LT, PD and AL. Advice should be given to suspicious children to avoid or delay the development of concomitant exotropia.